Effect of weather parameters on the seasonal incidence of maize stem borer(Chilo partellus) in the kharif season in the Gird region of Madhya Pradesh - SUMAN, SHIVANI; BHADAURIA, N S; NAVEEN; MAHORE, PRINCE; SEERVI, SITARAM; KUMAR, NEERAJ; TOMAR, NEHA (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during rainy (kharif ) seasons of 2021–22 and 2022–23 at College of Agriculture, Rajmata Vijayaraje Scindia Krishi Vishwa Vidyalaya, Gwalior, Madhya Pradesh to investigate the seasonal incidence of Chilo partellus and its correlation with weather parameters in the Gird region of Madhya Pradesh. The maize (Zea mays L.) variety RMH 1899 Super (Hybrid) was used for the experiment. The study revealed that the population of stem borer, C. partellus, larvae/plant was first recorded in early August during the 31st Standard Meteorological Week (SMW) and reached its peak in the third week of August during the 34th SMW. After the 41st SMW, no larvae were recorded in the crop during both years. From the 31st–36th SMW, the presence of dead hearts caused by C. partellus was noted, but no dead hearts were observed until the crops were harvested in both years. Additionally, plant damage due to C. partellus also began in the first week of August during the 31st SMW and reached a maximum in early September during the 36th SMW in both years. After the 41st SMW, no further plant damage occurred due to the reduced number of larvae in both consecutive years. During kharif 2021, the larval population of stem borer, dead heart % and plant damage % due to stem borer were significantly positively impacted by minimum temperature. During kharif 2022, the larval population of stem borer and plant damage % due to stem borer were significantly positively impacted by minimum temperature and evening relative humidity while none of the abiotic factors showed a significant correlation with the dead heart % in this year.